'Luckily, I don't believe in statistics': survey of women's understanding of chance of success with futile fertility treatments. Issue 2 (February 2021) - Miron-Shatz, Talya; Holzer, Hananel; Revel, Ariel; Weissman, Ariel; Tarashandegan, Danit; Hurwitz, Arye; Gal, Michael; Ben-chetrit, Avraham; Weintraub, Amir; Ravhon, Amir; Tsafrir, Avi
Abstract: Research question: Why are women who face poor prognoses for success in assisted reproductive technology (ART) treatment choosing to pursue procedures using their own eggs, despite receiving information that their chances of success are very low. Design: Cross-sectional study based on an anonymous questionnaire distributed to women aged between 43 and 45 years, undergoing ART using their own oocytes, at six public outpatient fertility clinics and three public in-hospital IVF units in Israel between 2015 and 2016. The main outcome measure was personal estimation of chance to achieve a live birth after the current ART treatment cycle and the cumulative estimated rate after all the treatment cycles the patient intended to undergo. Results: Response rate was 70.0%, with 91 participants of mean age 43.8 ± 0.7 years. Participants estimated their delivery rates after the next ART treatment cycle at 49.0 ± 31.8% (response rate 93.4%) and their cumulative delivery rates after all the ART treatments they would undergo at 57.7 ± 36.3% (response rate 90.1%). This is significantly higher than the predicted success rates of 5% and 15%, respectively (both P < 0.001), which are based on national register data. Nearly one-half of patients rated themselves as having a better than average chance of conception (47.3%). Conclusion: Women do not pursue futile treatments because they lack information. Despite being informed of the low success rates of conception using ART treatments, many patients of advanced maternal age have unrealistically high expectations from ART, essentially ignoring their estimated prognosis when deciding on treatment continuation. Future work should examine the psychological reasons behind continuing futile fertility treatments.